Evaluation of a psycho-educational parenthood transition program - Murta, Sheila Giardini; Rodrigues, Andréia Crispim; Rosa, Isabela de Oliveira; Paulo, Silvia Guimarães de (Paidéia (Ribeirão Preto), 2012)
This paper describes a needs assessment and a process evaluation of a longitudinal support program to first-time parents. A couple participated in a longitudinal intervention, with nine home visits, focused on the development of parental skills and couple empowerment. The baby-parents interaction and the couple's reactions to the intervention were video recorded and afterwards registered into the Process Evaluation Protocol. Data analysis showed that the couple felt satisfied with the program and used the information and strategies received, with a positive impact on the dimensions of conjugality, better communication and interpersonal problem solving and parenthood, development of knowledge on the infant's development, change in beliefs related to violent parental educational practices and responsiveness in the relationship between the baby and the parents, besides lower parental stress. Replications of this study in bigger samples with follow-up evaluations are recommended.